Concept of Law 07611 - H.L.A. Hart (Universal Publishing, 1994)
The Concept of Law is the most important and original work of legal philosophy written this century. First published in 1961, it is considered the masterpiece of H.L.A. Hart's enormous contribution to the study of jurisprudence and legal philosophy. Its elegant language and balanced argumentshave sparked wide debate and unprecedented growth in the quantity and quality of scholarship in this area--much of it devoted to attacking or defending Hart's theories. Principal among Hart's critics is renowned lawyer and political philosopher Ronald Dworkin who in the 1970s and 80s mounted aseries of challenges to Hart's Concept of Law. It seemed that Hart let these challenges go unanswered until, after his death in 1992, his answer to Dworkin's criticism was discovered among his papers.In this valuable and long-awaited new edition Hart presents an Epilogue in which he answers Dworkin and some of his other most influential critics including Fuller and Finnis. Written with the same clarity and candor for which the first edition is famous, the Epilogue offers a sharperinterpretation of Hart's own views, rebuffs the arguments of critics like Dworkin, and powerfully asserts that they have based their criticisms on a faulty understanding of Hart's work. Hart demonstrates that Dworkin's views are in fact strikingly similar to his own. In a final analysis, Hart'sresponse leaves Dworkin's criticisms considerably weakened and his positions largely in question. Containing Hart's final and powerful response to Dworkin in addition to the revised text of the original Concept of Law, this thought-provoking and persuasively argued volume is essential reading for lawyers and philosophers throughout the world.